Composition, trophic structure and activity patterns of the understory bats of the Bitaco Forest Reserve (2018)
The present study describes composition and trophic structure, and assesses the effect of environmental temperature and rainfall on the pattern of nocturnal activity of understory bats in an Andean forest, in the first half of the night. Seven sampling events were conducted, lasting six nights each one. Ten mist nets were used to capture bats, which were checked every hour between 18:00 and 00:00 hours. Bat species, sex and capture time were registered. In addition, environmental temperature and rainfall were also recorded during sampling. The bat assemblage of the understory of the study area was represented mostly by frugivore species, within this guild there was a lower richness of nomadic than sedentary species. For the first half of the night, bat activity peaked between 18:00 and 19:00 hours and declined to a minimum level between 22:00 and 23:00 hours. The most accurate model to explain variation in bat captures included only the effect of air temperature, which positively affected the number of captures. In conclusion, for the sampled period the activity of the bat assemblage in the study area was not related to rainfall and exhibited a slight but significant relationship with air temperature.